Managing the South China Sea Dispute: Multilateral and Bilateral Approaches. (28th March 2022) - Peng, Nian; Ngeow, Chow Bing
Abstract: This article investigates and examines the efficacy of the multilateral and bilateral modalities or mechanisms in managing the South China Sea dispute between China and Association of Southeast Asian Nations (ASEAN) claimant states. There are three multilateral modalities in the management and control of the South China Sea dispute: the "ASEAN + China, " "ASEAN + X" and "ASEAN-X" modalities. At the bilateral level, mechanisms have developed between China and the Philippines, China and Vietnam, and China and Malaysia. It is argued in this article that the "ASEAN + China" modality remains the most realistic multilateral arrangement currently, while the alternative options of "ASEAN + X" and "ASEAN-X" might be feasible in the long term. Meanwhile, while bilateral mechanisms have fostered trust building and pragmatic maritime cooperation in the South China Sea, they are facing a number of challenges.